Metabolomics reveals the role of PPARα in Tripterygium Wilfordii-induced liver injury. (10th May 2022) - Dai, Manyun; Peng, Wan; Zhang, Ting; Zhao, Qi; Ma, Xiaofang; Cheng, Yan; Wang, Chunyan; Li, Fei
Abstract: Ethnopharmacological relevance: Tripterygium glycosides tablets (TGT) and Tripterygium wilfordii tablets (TWT) have been used to treat autoimmune diseases clinically, however, the side effects of TWT are higher than TGT, especially for hepatotoxicity. The aim of the study: This study aims to determine the mechanism of TWT-induced liver injury. Materials and methods: We performed metabolomic analysis of samples from mice with liver injury induced by TGT and TWT. Ppara -null mice were used to determine the role of PPARα in TWT-induced liver injury. Results: The results indicated that TWT induced the accumulation of medium- and long-chain carnitines metabolism, which was associated with the disruption of PPARα-IL6-STAT3 axis. PPARα agonists fenofibrate could reverse the liver injury from TWT and TP/Cel, and its protective role could be attenuated in Ppara -null mice. The toxicity difference of TWT and TGT was due to the different ratio of triptolide (TP) and celastrol (Cel) in the tablet in which TP/Cel was lower in TWT than TGT. The hepatotoxicity induced by TP and Cel also inhibited PPARα and upregulated IL6-STAT3 axis, which could be alleviated following by PPARα activation. Conclusions: These results indicated that PPARα plays an important role in the hepatotoxicity of Tripterygium wilfordii, and PPARα activation may offer a promising approach to prevent hepatotoxicity induced by the preparations of Tripterygium wilfordii . Graphical abstract: Image 1